MEASUREMENT OF OPERATIONAL QUANTITIES Hp(0.07) AND Hp(3) FOR INDIGENOUSLY DEVELOPED 106Ru/106Rh SOURCE USING AN EXTRAPOLATION CHAMBER. Issue 3 (27th March 2019) - Vandana, S; Bakshi, A K; Behrens, R; Chattaraj, A; Saxena, S K; Dhami, P S; Panja, S; Jagasia, P; Selvam, T Palani; Dash, A; Datta, D
Abstract: In the present study, a prototype 106 Ru/ 106 Rh source was fabricated using high level liquid waste from reactor fuel, fixed in a stainless steel housing with a window and backing made of silver. The study involves measurement of the operational quantities H p (0.07), H p (3) and the percentage depth dose (PDD) using an extrapolation chamber. It also involves determination of necessary correction factors to arrive at H p (0.07) and H p (3) following International Organisation for Standardisation (ISO) and methods suggested in literature. The study facilitates incorporation of the 106 Ru/ 106 Rh source as a beta reference source for quality assurance programme in TLD personnel monitoring as per the guidelines of ISO.